Evaluation of the variation in chemical composition and surface topography of different brands of gutta percha cones - (:unkn) unknown (My University, 1992)
There have been many studies on the gutta percha cones used in endodontic therapy. Variations exist between different brands of cone. Since an appropriate cone plays a very important role in the prognosis of therapy, this study examined the surface topography and chemical composition of eight different brands of cone by, a scanning electron microscopy (SEM) and atomic absorption spectrometry. There were some differences between all brands of gutta percha cones.
Keywords: Microscopy, Electron, Scanning; Surface Properties; Gutta-Percha; Zinc Oxide